Implementation Organizing the Umrah Pilgrimage Based on Constitution Number 8 of 2019 at PT Al Fajr Yogyakarta - Rizka Syahmouzi Lubis; Syafiq Mahmadah Hanafi (Jurnal Eduslamic, 2026)
Indonesia is one of the countries with the largest number of Umrah pilgrims in the world, requiring Umrah Travel Organizers (PPIU) to implement Law Number 8 of 2019 to ensure the protection and quality of services for pilgrims. This study aims to analyze the implementation of Law Number 8 of 2019 at PT Al Fajr Yogyakarta. The study used a descriptive qualitative approach with George C. Edward III's policy implementation theory. Data were obtained through observation, semi-structured interviews, and documentation, then analyzed using an interactive analysis model with source and technique triangulation. The results show that PT Al Fajr Yogyakarta has implemented the provisions of Law Number 8 of 2019 by fulfilling aspects of legality, service, guidance, worship assistance, and pilgrim protection. This implementation improves service quality and strengthens public trust in the organization of the Umrah pilgrimage. This study demonstrates that compliance with regulations is a critical factor in achieving quality Umrah pilgrimage implementation.